Formation of nanosized grain structure in martensitic 100Cr6 bearing steels upon rolling contact loading studied by atom probe tomography. Issue 11 (23rd July 2016) - Li, Y. J.; Herbig, M.; Goto, S.; Raabe, D.
Abstract : To understand the origin of white etching cracks (WECs), a systematic microstructural characterisation in the regions affected from the near-surface region down to the subsurface layers where WECs occur is necessary. As a starting point, we focus on the near-surface region of an axial thrust bearing, made of martensitic 100Cr6 steel, to study the influence of rolling contact loading on the microstructure and the resulting distributions of the major alloying elements C and Cr using atom probe tomography. We find that upon rolling contact loading the original plate-like martensitic structure evolves into a nanosized equiaxed grain structure with C segregation up to 5 at.-% at the grain boundaries. Cementite particles, located at grain boundaries and triple junctions, undergo spheroidisation. The originally homogeneously distributed Cr becomes enriched in spheroidised cementite particles. The microstructural changes give strong hints that rolling contact loading induces plastic deformation and an increased temperature on the near-surface region. This paper is part of a Themed Issue on Recent developments in bearing steels.